Insights into Acinetobacter baumannii: A Review of Microbiological, Virulence, and Resistance Traits in a Threatening Nosocomial Pathogen - Carole Ayoub Moubareck; Dalal Hammoudi Halat (MDPI AG, 2020)
Being a multidrug-resistant and an invasive pathogen, Acinetobacter baumannii is one of the major causes of nosocomial infections in the current healthcare system. It has been recognized as an agent of pneumonia, septicemia, meningitis, urinary tract and wound infections, and is associated with high mortality. Pathogenesis in A. baumannii infections is an outcome of multiple virulence factors, including porins, capsules, and cell wall lipopolysaccharide, enzymes, biofilm production, motility, and iron-acquisition systems, among others. Such virulence factors help the organism to resist stressful environmental conditions and enable development of severe infections. Parallel to increased prevalence of infections caused by A. baumannii, challenging and diverse resistance mechanisms in this pathogen are well recognized, with major classes of antibiotics becoming minimally effective. Through a wide array of antibiotic-hydrolyzing enzymes, efflux pump changes, impermeability, and antibiotic target mutations, A. baumannii models a unique ability to maintain a multidrug-resistant phenotype, further complicating treatment. Understanding mechanisms behind diseases, virulence, and resistance acquisition are central to infectious disease knowledge about A. baumannii. The aims of this review are to highlight infections and disease-producing factors in A. baumannii and to touch base on mechanisms of resistance to various antibiotic classes.